2021
DOI: 10.1111/mmi.14799
|View full text |Cite
|
Sign up to set email alerts
|

RNA‐binding protein Hfq downregulates locus of enterocyte effacement‐encoded regulators independent of small regulatory RNA in enterohemorrhagic Escherichia coli

Abstract: Enterohemorrhagic Escherichia coli (EHEC) causes severe human diseases worldwide. The type 3 secretion system and effector proteins are essential for EHEC infection, and are encoded by the locus of enterocyte effacement (LEE). RNA‐binding protein Hfq is essential for small regulatory RNA (sRNA)‐mediated regulation at a posttranscriptional level and full virulence of many pathogenic bacteria. Although two early studies indicated that Hfq represses LEE expression by posttranscriptionally controlling the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 94 publications
2
7
0
Order By: Relevance
“…While these results provide an additional confirmation of Hfq involvement in the regulation of RecB translation, they do not strongly support a sRNA-dependent mechanism. This is consistent with recent studies demonstrating examples of direct regulation by Hfq in a sRNA-independent manner [106,17,104,31,90]. We nevertheless looked for potential candidates of sRNAs, using the available Hfq RIL-seq and CLASH datasets [65,46].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While these results provide an additional confirmation of Hfq involvement in the regulation of RecB translation, they do not strongly support a sRNA-dependent mechanism. This is consistent with recent studies demonstrating examples of direct regulation by Hfq in a sRNA-independent manner [106,17,104,31,90]. We nevertheless looked for potential candidates of sRNAs, using the available Hfq RIL-seq and CLASH datasets [65,46].…”
Section: Discussionsupporting
confidence: 81%
“…Based on the localisation of the Hfq-binding uncovered in the CRAC data, we further propose a mechanism of Hfqdependent modulation of translational initiation of RecB (fig. 5A) (similarly to the models of Hfq regulation suggested recently [31,17,106]).…”
Section: Hfq Regulates Recb Expressionmentioning
confidence: 54%
See 1 more Smart Citation
“… 51 In vitro analyses revealed that the Hfq distal face directly binds near the translational initiation site of the grlA mRNA and inhibits its translation in an sRNA-independent manner in EHEC O157:H7. 52 It is therefore conceivable that Hfq can indirectly activate EHEC O157:H7 motility and flagellar gene expression through post-transcriptional regulation of qseBC and grlA .…”
Section: Post-transcriptional and Post-translational Regulatory Prote...mentioning
confidence: 99%
“…The ClpXP complex, an AAA + protease, positively controls LEE gene expression in EHEC through direct regulation of GrlR levels during the stationary phase of growth ( Iyoda and Watanabe, 2005 ). Moreover, Hfq, an RNA chaperone, together with the small RNAs MgrR, RyhB and McaS, negatively modulate LEE gene expression in EPEC at the post-transcriptional level by destabilizing the grlRA mRNA and, consequently, the expression of GrlR and GrlA ( Hansen and Kaper, 2009 ; Bhatt et al, 2017 ; Sudo et al, 2022 ). Furthermore, GrlA and GrlR also regulate the expression of genes located outside the LEE, such as the hemolysin and flagellar genes in EHEC ( Iyoda et al, 2006 ; Saitoh et al, 2008 ), as well as some non-LEE encoded effector genes in EPEC ( Garcia-Angulo et al, 2012 ), indicating that during the evolution of A/E organisms other genes were incorporated into the Ler-GrlRA regulatory network to coordinate other functions that enhanced the pathogenic capabilities of these bacteria.…”
Section: Introductionmentioning
confidence: 99%